Evaluation of wireless bat swing speed sensors - Lyu, B.; Smith, L. V. (Sports Engineering, 2018)
Batter swing speed is an important parameter in understanding the performance of baseball and softball players. A number of swing speed sensors have recently been introduced and are commercially available. The aim of this study was to compare three wireless swing sensors with high speed video. Swing speed from high speed video was measured by differentiating the position coordinates of tracking markers on the bat barrel. On average, the wireless bat swing sensors reported speeds 8% slower than that found from video tracking. The agreement was better at low swing speeds, suggesting that the current generation of wireless sensors is best suited for developing players. Spatial measures, such as swing angle, were not in good agreement with video tracking.